The Effect of Service Quality, Learning Quality, and Promotion Strategy on Parents' Decisions in Choosing ABC Primary Schools - Soegeng Wahyoedi; Saparso Saparso; Melitina Tecoalu; Hery Winoto Tj (Budapest International Research and Critics University, 2021)
To survive in the competition, educational institutions must maintain the quality both in terms of the teaching staff used and in terms of the learning provided to students. This study examines the effect of service quality, learning quality, and promotion strategies on parents' decisions in choosing primary schools for their children. Purposive sampling technique was used in the data collection process, where the respondents were the parents of students from ABC primary school as many as 100 respondents. The test results show that the quality of the teaching staff, the quality of the learning methods used, and the school's promotion strategies are essential aspects that parents consider in determining the primary school for their children.